The effect of excitation and preparation pulses on nonslice selective 2D UTE bicomponent analysis of bound and free water in cortical bone at 3T. Issue 2 (27th January 2014) - Li, Shihong; Chang, Eric Y.; Bae, Won C.; Chung, Christine B.; Hua, Yanqing; Zhou, Yi; Du, Jiang
Abstract : Purpose: : The purpose of this study was to investigate the effect of excitation, fat saturation, long T2 saturation, and adiabatic inversion pulses on ultrashort echo time (UTE) imaging with bicomponent analysis of bound and free water in cortical bone for potential applications in osteoporosis. Methods: : Six bovine cortical bones and six human tibial midshaft samples were harvested for this study. Each bone sample was imaged with eight sequences using 2D UTE imaging at 3T with half and hard excitation pulses, without and with fat saturation, long T2 saturation, and adiabatic inversion recovery (IR) preparation pulses. Single‐ and bicomponent signal models were utilized to calculate the T2 * s and/or relative fractions of short and long T2 * s. Results: : For all bone samples UTE T2 * signal decay showed bicomponent behavior. A higher short T2 * fraction was observed on UTE images with hard pulse excitation compared with half pulse excitation (75.6% vs 68.8% in bovine bone, 79.9% vs 73.2% in human bone). Fat saturation pulses slightly reduced the short T2 * fraction relative to regular UTE sequences (5.0% and 2.0% reduction, respectively, with half and hard excitation pulses for bovine bone, 6.3% and 8.2% reduction, respectively, with half and hard excitation pulses for human bone). Long T2 saturation pulses significantly reduced the long T2 * fraction relative to regular UTE sequence (18.9% and 17.2% reduction, respectively, with half and hard excitation pulses for bovine bone, 26.4% and 27.7% reduction, respectively, with half and hard excitation pulses for human bone). With IR‐UTE preparation the long T2 * components were significantly reduced relative to regular UTE sequence (75.3% and 66.4% reduction, respectively, with half and hard excitation pulses for bovine bone, 87.7% and 90.3% reduction, respectively, with half and hard excitation pulses for human bone). Conclusions: : Bound and free water T2 * s and relative fractions can be assessed using UTE bicomponent analysis. Long T2 * components are affected more by long T2 saturation and IR pulses, and short T2 * components are affected more by fat saturation pulses.